Molecular catalyst modified by amorphous polytetrafluoroethylene as well as preparation method and application of molecular catalyst
By reducing the crystallinity of PTFE to form amorphous sheets and modifying the molecular catalyst, the problem of reduced CO selectivity under high current density is solved, efficient CO2 reduction to CO is achieved, and the industrial application of CO2RR technology is supported.
Patent Information
- Application Number
- CN202310911335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-24
AI Technical Summary
Under high current density, the CO selectivity of molecular catalysts decreases, resulting in an increase in hydrogen reaction, and it is impossible to achieve industrial promotion and application.
By controlling the processing temperature, the crystallinity of polytetrafluoroethylene (PTFE) is reduced, so that PTFE collapses from a three-dimensional spherulite structure into an amorphous sheet, and the molecular catalyst is modified to form a micron sheet-shaped solid-supported cobalt phthalocyanine catalyst.
The concentration of carbon dioxide at the catalyst interface has been increased, and the reaction interface has transformed from Wimbled to Casey, achieving 98%of CO Faraday efficiency, and maintaining higher CO selectivity at large current density.
Smart Images

Figure CN119352095A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis, and in particular, relates to a catalyst for electrocatalytic reduction of carbon dioxide to produce carbon monoxide, and a preparation method and application thereof. Background Art
[0002] Due to the massive consumption of fossil fuels, CO2 emissions accumulate in the atmosphere year by year. The electrochemical CO2 reduction reaction (CO2RR) is a key technology to achieve carbon neutrality and a closed-loop carbon cycle. Due to the tunability and remarkable electronic structure of molecular catalysts, catalytic performance comparable to that of metal catalysts can be achieved at significantly lower loading levels. Therefore, in recent years, the rational design and optimization of molecular catalysts for their application in CO2RR has attracted widespread attention (E.Boutin, M.Wang, JC Lin, M.Mesnage, D.Mendoza, B.Lassalle-Kaiser, C.Hahn, T.F.Jaramillo, M.Robert, Aqueous Electrochemical Reduction of Carbon Dioxide and Carbon Monoxide into Methanol with Cobalt Phthalocyanine, Angew.Chem.Int.Ed.58(2019)1433-7851; Z.Jiang, Z.Zhang, H.Li, Y.Tang, Y.Yuan, J.Zao, H.Zheng, Y.Liang, Molecular Catalyst with Near 100% Selectivity for CO2Reduction in Acidic Electrolytes, Advanced Energy Materials.13(2023)2203603; B:Environmental.268(2020)118452).
[0003] The research on molecular catalysts can be divided into homogeneous catalysis and heterogeneous catalysis (Y.Wu, Y.Liang, H.Wang, Heterogeneous Molecular Catalysts of Metal Phthalocyanines for Electrochemical CO2 Reduction Reactions, Acc.Chem.Res.54(2021)3149-3159). Compared with homogeneous catalysis in which catalyst molecules shuttle around the electrode, heterogeneous catalysis has faster electron transfer speed (X. Zhang, Y. Wang, M. Gu, M. Wang, Z. Zhang, W. Pan, Z. Jiang, H. Zheng, M. Lucero, H. Wang, G. E. Sterbinsky, Q. Ma, Y.-G. Wang, Z. Feng, J. Li, H. Dai, Y. Liang, Molecular Engineering of Dispersed Nickel Phthalocyanines on Carbon Nanotubes for Selective CO2 Reduction, Nat Energy. 5 (2020) 684-692) and higher catalyst spatial density (A. J. S. Tharum, C. P. Kubiak, Kinetics and Limiting Current Densities of Homogeneous and Heterogeneous Electrocatalysts, J.Phys.Chem.Lett.2(2011)2372-2379) and lower electrolyzer requirements (T.Burdyny, WA Smith, CO2 Reduction on Gas-Diffusion Electrodes and Why Catalytic Performance Must Be Assessed at Commercially-Relevant Conditions, Energy Environ.Sci.12(2019)1442-1453). Therefore, fixing molecular catalysts on carbon nanotubes is a commonly used heterogeneous catalytic strategy, and exhibits nearly 100% CO selectivity at low current (
[0004] ANMarianov,Y.Jiang,Mechanism-Driven Design of HeterogeneousMolecular Electrocatalysts for CO2 Reduction,Acc.Mater.Res.3(2022)620-633;L.Sun,V.Reddu,S.Xi,C.Dai,Y.Sheng,T.Su,ACFisher,X.Wang,Cobalt QuaterpyridineComplexes for Highly Efficient Heterogeneous CO2 Reduction in Aqueous Media,Advanced Energy Materials.12(2022)2202108; NanotubeHybrid Structures,Nat Commun.8(2017)14675). However, when the current density increases, protons occupy a large number of active sites, resulting in an increase in the hydrogen generation reaction (HER) and a decrease in CO selectivity (P.Yue, Q.Fu, J.Li, L.Zhang, L.Xing, Z.Kang, Q.Liao, X.Zhu, Triple-Phase Electrocatalysis for The Enhanced CO2Reduction to HCOOH on A Hydrophobic Surface, Chemical Engineering Journal.405(2021)126975). At a current density of 75 mA / cm 2When the Faraday efficiency of immobilized molecular catalyst CO is less than 80%, it cannot be promoted and applied in industry. A feasible strategy is to inhibit proton transfer by adjusting the hydrophobicity of active sites, increase the local concentration of CO2 (JA Rabinowitz, DS Ripatti, RG Mariano, MW Kanan, Improving the Energy Efficiency of CO Electrolysis by Controlling Cu Domain Size in Gas Diffusion Electrodes, ACS Energy Lett. 7 (2022) 4098-4105), promote the formation of solid-liquid-gas three-phase interface (L. Xiong, X. Fu, Y. Zhou, P. Nian, Z. Wang, Q. Yue, Precise Site-Hydrophobicity Modulation for Boosting High-Performance CO2 Electroreduction, ACS Catal. (2023) 6652-6660), and finally achieve the selective reduction of CO2 to CO.
[0005] Therefore, how to adjust the hydrophobic morphology of molecular catalysts by controlling key process parameters, thereby improving the CO2 concentration at the reaction interface and inhibiting the occurrence of hydrogen evolution reaction at high current density is of great significance and remains a key technical problem that needs to be solved urgently. Summary of the invention
[0006] The present invention aims to control the hydrophobic morphology of molecular catalysts, and provides an amorphous polytetrafluoroethylene (PTFE) modified molecular catalyst and its synthesis and application, mainly by controlling the processing temperature, reducing the PTFE crystallinity, and causing the PTFE three-dimensional spherulite structure to collapse to form amorphous flaky PTFE. The micron flaky catalyst has a certain interception effect on the raw gas CO2, increases the CO2 concentration at the catalytic interface, and promotes the transition of the contact interface from the Wenzel state to the Casey state, and can be well applied to the field of electrocatalytic CO2 reduction.
[0007] The technical purpose of the present invention is achieved through the following technical solutions.
[0008] An amorphous polytetrafluoroethylene-modified molecular catalyst, a hydrophobic immobilized cobalt phthalocyanine catalyst using micron-sized polytetrafluoroethylene flakes, is prepared according to the following steps:
[0009] The carbon nanotubes hydrophobized by micron-sized polytetrafluoroethylene and cobalt phthalocyanine are mixed in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, and the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and after washing and drying, an amorphous polytetrafluoroethylene-modified molecular catalyst is obtained, wherein:
[0010] After polytetrafluoroethylene and carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry material, and after standing and drying at room temperature, powdered polytetrafluoroethylene hydrophobic carbon nanotubes are obtained; the powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature of 20-30 degrees Celsius to 400-450 degrees Celsius at a speed of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept warm for 1-3 hours, and then cooled to room temperature of 20-30 degrees Celsius with the furnace to obtain micron-sheet polytetrafluoroethylene hydrophobic carbon nanotubes; after polytetrafluoroethylene and carbon nanotubes are mixed, the mass percentage of polytetrafluoroethylene is 10-30wt%.
[0011] Furthermore, after the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 20 wt %.
[0012] Furthermore, the mass ratio of the carbon nanotubes made hydrophobic by micron-sheet polytetrafluoroethylene to cobalt phthalocyanine is 15:1.
[0013] Furthermore, the amount of N,N-dimethylformamide added is (20-25) ml per mg of cobalt phthalocyanine.
[0014] Furthermore, the inert protective atmosphere is nitrogen, argon or helium.
[0015] Furthermore, the powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature 20-30 degrees Celsius to 400-430 degrees Celsius at a rate of 5-10 degrees Celsius per minute in an inert protective atmosphere and kept at this temperature for 2-3 hours, and then cooled to room temperature 20-30 degrees Celsius in the furnace.
[0016] The invention discloses an application of the molecular catalyst modified with amorphous polytetrafluoroethylene in the electrocatalytic reduction of carbon dioxide to produce carbon monoxide.
[0017] When used, the amorphous polytetrafluoroethylene-modified molecular catalyst (i.e., the immobilized cobalt phthalocyanine catalyst of the present invention), FAA solution and DMF are mixed into a uniform solution, which is sprayed on the gas diffusion electrode as the working electrode (i.e., the catalytic electrode) with a loading of 1-3 mg / cm 2 , using nickel foam loaded with iridium oxide as a counter electrode, power is applied to carry out an electrocatalytic reaction; the electrolyte used is an alkaline solution, such as a 1 mol / L KOH aqueous solution.
[0018] Compared with the prior art, the specific beneficial effects of the present invention are as follows:
[0019] (1) The present invention reduces the crystallinity of the hydrophobic agent PTFE by controlling the temperature, and develops from a three-dimensional spherulite to a two-dimensional amorphous state. The change in crystallinity makes the contact between PTFE and CNT better, which further improves the hydrophobicity of the catalyst carrier. At the same time, the conductivity of PTFE increases, so that the tank pressure does not increase too much.
[0020] (2) The present invention constructs a micron-shaped immobilized molecular catalyst. The micron-shaped sheet will form a "gas chamber" during CO2RR, which has the function of trapping CO2, increasing the CO2 concentration at the interface, and promoting the reaction interface from the Wenzel state dominated by the solid-liquid interface to the Casey state dominated by the solid-gas interface, achieving a CO Faraday efficiency of 98%.
[0021] (3) The HT-PTFE-CoPc / CNT catalyst of the present invention has a simple production route, low preparation cost and easy-to-achieve reaction conditions. It can maintain high CO selectivity at high current density and maintain good economic benefits due to low cost, providing important scientific and technological support for the industrialization of CO2RR technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the synthesis route of HT-PTFE-CoPc / CNT obtained in Example 2.
[0023] Figure 2 This is the SEM characterization result of HT-PTFE-CoPc / CNT obtained in Example 2.
[0024] Figure 3 This is the EDS characterization result diagram of HT-PTFE-CoPc / CNT obtained in Example 2.
[0025] Figure 4 It is the CLSM characterization result diagram of HT-PTFE-CoPc / CNT obtained in Example 1 and Example 2.
[0026] Figure 5 This is the XRD characterization result diagram of the cobalt phthalocyanine catalyst obtained in Example 1-2.
[0027] Figure 6 This is a graph showing the contact angle test results of the cobalt phthalocyanine catalyst obtained in Example 1-2.
[0028] Figure 7 This is a characterization diagram of the Faraday efficiency of the electrocatalytic CO2 reduction product CO obtained by the cobalt phthalocyanine catalyst obtained in Example 1-2.
[0029] Figure 8This is a characterization diagram of the local current density of CO, the product of the electrocatalytic CO2 reduction using the cobalt phthalocyanine catalyst obtained in Example 1-2.
[0030] Fig. 9 This is a characterization diagram of the Faraday efficiency of the electrocatalytic CO2 reduction product CO obtained by the cobalt phthalocyanine catalyst obtained in Examples 1-4.
[0031] Fig.10 This is a characterization diagram of the stability test of the CO product of the HT-PTFE-CoPc / CNT electrocatalytic CO2 reduction obtained in Example 2. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0033] It should be noted that the invention patent previously applied for by this research group, "A highly hydrophobic molecular catalyst, its preparation method and application", has application number 2023108872318 and application date July 19, 2023 (prior application). It uses hydrophobic materials for modification, but the research group failed to regulate the hydrophobic morphology. Later, based on previous research, high-temperature treatment was carried out in order to change the hydrophobic morphology. In this application, the basic ideas of the prior application are adopted for improvement. For any incompleteness, please refer to the prior application.
[0034] Example 1
[0035] Accurately weigh 15 mg of carbon nanotubes and 1 mg of cobalt phthalocyanine in a beaker, add 20 mL of N,N-dimethylformamide (DMF), ultrasonically treat for 30 min, centrifuge at 7000 r / min for 3 min, remove the supernatant, wash the obtained solid with DMF, ethanol and deionized water in turn, and dry in an oven at 80°C for 10 h to obtain immobilized cobalt phthalocyanine (CoPc / CNT).
[0036] Example 2
[0037] (1) Accurately weigh 20 mg of carbon nanotubes and spread them evenly in a beaker. Take 5.6 μL of PTFE emulsion (i.e., a suspended aqueous solution of PTFE) with a mass concentration of 0.9 g / mL and dilute it to 200 μL with deionized water. Add the diluted emulsion dropwise into the beaker and perform ultrasonication for 10 min to uniformly mix the emulsion and carbon nanotubes to form a slurry (the mass fraction of PTFE in the solid is 20 wt%, i.e., the mass of PTFE / the sum of the mass of PTFE and the mass of carbon nanotubes).
[0038] (2) The obtained slurry mixture was allowed to stand at room temperature of 20-30 degrees Celsius overnight (8 hours), and dried in an oven at 80 degrees Celsius for 10 hours to obtain PTFE-CNT (20 wt%).
[0039] (3) The obtained PTFE-CNT was heated from room temperature (20-30 degrees Celsius) to 400°C at a rate of 10 degrees Celsius per minute in a nitrogen atmosphere, and the high temperature treatment was carried out for 2 hours, and then slowly annealed to room temperature in a tubular furnace to obtain HT-PTFE-CNT.
[0040] (4) 15 mg of HT-PTFE-CNT powder and 1 mg of cobalt phthalocyanine were mixed in a beaker, 20 mL of N,N-dimethylformamide (DMF) was added, and ultrasonic treatment was performed for 30 min. After centrifugation at 7000 r / min for 3 min, the supernatant was removed, and the solid was washed with DMF, ethanol, and deionized water in turn, and dried in an oven at 80 °C for 10 h to obtain HT-PTFE-CoPc / CNT.
[0041] Figure 1 This is the synthesis route of HT-PTFE-CoPc / CNT obtained in Example 2. Figure 2 This is a scanning electron microscope image of the HT-PTFE-CoPc / CNT obtained in Example 2, in which the PTFE presents a micron-flaky morphology. Figure 3 This is the energy spectrum of HT-PTFE-CoPc / CNT obtained in Example 2. It can be seen that the F element is evenly distributed, that is, PTFE forms an amorphous state and is evenly dispersed. Figure 4 This is the laser confocal scanning electron microscopy characterization image of HT-PTFE-CoPc / CNT obtained in Example 1 and Example 2. It can be seen that the fluorescence intensity decays slowly and the contact interface transforms from the Wenzel state to the Casey state. Reference Shi, R et al. Efficient Wettability-Controlled Electroreduction of CO2 to CO at Au / C Interfaces. Nat Commun 11, 3028 (2020). Figure 5 The X-ray diffraction characterization results of the cobalt phthalocyanine catalysts obtained in Examples 1-2 show that the peak value of PTFE in Example 2 is relatively low, indicating that the crystallinity of PTFE decreases after high-temperature annealing, forming an amorphous state. Figure 6 The contact angle test results of the cobalt phthalocyanine catalysts obtained in Examples 1-2 are shown. The contact angle of Example 2 is significantly greater than that of Example 1, indicating that the amorphous flaky PTFE significantly improves the hydrophobicity of the catalyst.
[0042] Example 3
[0043] (1) Accurately weigh 20 mg of carbon nanotubes and spread them evenly in a beaker. Take 2.5 μL of PTFE emulsion (i.e., a suspended aqueous solution of PTFE) with a mass concentration of 0.9 g / mL and dilute it to 200 μL with deionized water. Add the diluted emulsion dropwise into the beaker and perform ultrasonication for 10 min to uniformly mix the emulsion and carbon nanotubes to form a slurry (the mass fraction of PTFE in the solid is 10 wt%, i.e., the mass of PTFE / the sum of the mass of PTFE and the mass of carbon nanotubes).
[0044] (2) The obtained slurry mixture was allowed to stand at room temperature of 20-30 degrees Celsius overnight (8 hours), and dried in an oven at 80 degrees Celsius for 10 hours to obtain PTFE-CNT (10 wt%).
[0045] (3) The obtained PTFE-CNT was heated from room temperature (20-30 degrees Celsius) to 430°C at a rate of 10 degrees Celsius per minute in a nitrogen atmosphere, and the high temperature treatment was carried out for 3 hours, and then slowly annealed to room temperature in a tubular furnace to obtain HT-PTFE-CNT (10wt%).
[0046] (4) Take 15 mg of HT-PTFE-CNT powder and 1 mg of cobalt phthalocyanine in a beaker, add 20 mL of N,N-dimethylformamide (DMF), ultrasonically treat for 30 min, centrifuge at 7000 r / min for 3 min, remove the supernatant, wash the obtained solid with DMF, ethanol, and deionized water in turn, and dry in an oven at 80°C for 10 h to obtain PTFE-CoPc / CNT (10 wt%).
[0047] Example 4
[0048] (1) Accurately weigh 20 mg of carbon nanotubes and spread them evenly in a beaker. Take 8.6 μL of PTFE emulsion (i.e., a suspended aqueous solution of PTFE) with a mass concentration of 0.9 g / mL and dilute it to 200 μL with deionized water. Add the diluted emulsion dropwise into the beaker and ultrasonicate for 10 min to uniformly mix the emulsion and carbon nanotubes to form a slurry (the mass fraction of PTFE in the solid is 30 wt%, i.e., the mass of PTFE / the sum of the mass of PTFE and the mass of carbon nanotubes).
[0049] (2) The obtained slurry mixture was allowed to stand at room temperature of 20-30 degrees Celsius overnight (8 hours), and dried in an oven at 80 degrees Celsius for 10 hours to obtain PTFE-CNT (30 wt%).
[0050] (3) The obtained PTFE-CNT was heated from room temperature (20-30 degrees Celsius) to 450°C at a rate of 10 degrees Celsius per minute in a nitrogen atmosphere, and the high temperature treatment was carried out for 1 hour, and then slowly annealed to room temperature in a tubular furnace to obtain HT-PTFE-CNT (30wt%).
[0051] (4) Take 15 mg of HT-PTFE-CNT powder and 1 mg of cobalt phthalocyanine in a beaker, add 20 mL of N,N-dimethylformamide (DMF), ultrasonically treat for 30 min, centrifuge at 7000 r / min for 3 min, remove the supernatant, wash the obtained solid with DMF, ethanol, and deionized water in turn, and dry in an oven at 80°C for 10 h to obtain PTFE-CoPc / CNT (30 wt%).
[0052] Example 5
[0053] (1) 10 mg of the cobalt phthalocyanine catalyst prepared in Example 1-4, 80 μL of FAA solution (purchased from Fuel Cell Store, with a mass percentage of 25 wt%), and 10 mL of DMF were mixed in a beaker and ultrasonically treated for 30 min to form a uniform mixed solution. The mixed solution was sprayed onto a 2×2 cm 2 The gas diffusion electrode was weighed on an analytical balance before and after spraying to control the solid loading of the electrode to 1.5 mg / cm 2 .
[0054] (2) The performance of the catalytic electrode was tested using a membrane electrode reactor. The membrane electrode reactor used was referenced by Zhang, G. et al. Efficient CO2 Electroreduction on Facet-Selective Copper Films with High Conversion Rate. Nat Commun 12, 5745 (2021). The test electrolyte was 1 mol / L KOH solution and the electrode area was 4 cm 2 , the product enters the gas chromatography for detection.
[0055] The CO Faraday efficiency values of the cobalt phthalocyanine catalyst prepared in Example 1-2 at different test current densities are as follows: Figure 7 As shown in the figure, it can be seen that the high temperature treatment makes PTFE and CNT combine well, the flake catalyst forms a "gas chamber" to trap CO2 to increase the CO2 concentration at the interface, and HT-PTFE-CoPc / CNT still maintains a high reaction selectivity at high current density. The local current density of CO of the cobalt phthalocyanine catalyst prepared in Example 1-2 at different test current densities is shown in Figure 8 As shown, it has a similar law to the change of CO Faraday efficiency. The CO Faraday efficiency values of the cobalt phthalocyanine catalysts prepared in Examples 1-4 at different test current densities are shown in Fig. 9As shown in the figure, it can be seen that the optimal content of PTFE in the hydrophobic immobilized cobalt phthalocyanine catalyst of micron-shaped PTFE flakes is 20wt%, at which time the catalyst performance is optimal. The HT-PTFE-CoPc / CNT prepared in Example 2 has a high conductivity at 75mA / cm 2 The stability of the catalyst at the current density Fig.10 As shown, it can maintain more than 90% CO Faradaic efficiency and be stable for 3h.
[0056] According to the content of the present invention, the process parameters are adjusted to achieve the preparation of the amorphous polytetrafluoroethylene modified molecular catalyst in the present invention, and the performance is basically consistent with the present invention after testing. Although the preferred embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, which all belong to the protection scope of the present invention.
Claims
1. An amorphous polytetrafluoroethylene-modified molecular catalyst, characterized in that: The molecular catalyst is a hydrophobic immobilized cobalt phthalocyanine catalyst using micron-sized polytetrafluoroethylene flakes, and is prepared according to the following steps: The carbon nanotubes hydrophobized by micron-sized polytetrafluoroethylene and cobalt phthalocyanine are mixed in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, and the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and after washing and drying, an amorphous polytetrafluoroethylene-modified molecular catalyst is obtained, wherein: After polytetrafluoroethylene and carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry material, and after standing and drying at room temperature, powdered polytetrafluoroethylene hydrophobic carbon nanotubes are obtained; the powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature of 20-30 degrees Celsius to 400-450 degrees Celsius at a speed of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept warm for 1-3 hours, and then cooled to room temperature of 20-30 degrees Celsius with the furnace to obtain micron-sheet polytetrafluoroethylene hydrophobic carbon nanotubes; after polytetrafluoroethylene and carbon nanotubes are mixed, the mass percentage of polytetrafluoroethylene is 10-30wt%.
2. The amorphous polytetrafluoroethylene-modified molecular catalyst according to claim 1, characterized in that: After the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 20 wt %.
3. The amorphous polytetrafluoroethylene-modified molecular catalyst according to claim 1, characterized in that: The mass ratio of carbon nanotubes hydrophobized by micron-sheet polytetrafluoroethylene to cobalt phthalocyanine is 15:
1.
4. The amorphous polytetrafluoroethylene-modified molecular catalyst according to claim 1, characterized in that: The amount of N,N-dimethylformamide added is (20-25) ml per mg of cobalt phthalocyanine.
5. The amorphous polytetrafluoroethylene modified molecular catalyst according to claim 1, characterized in that: The inert protective atmosphere is nitrogen, argon or helium.
6. The amorphous polytetrafluoroethylene modified molecular catalyst according to claim 1, characterized in that: The powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature (20-30 degrees Celsius) to 400-430 degrees Celsius at a rate of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept warm for 2-3 hours, and then cooled to room temperature (20-30 degrees Celsius) in the furnace.
7. A method for preparing an amorphous polytetrafluoroethylene-modified molecular catalyst, characterized in that: Prepare according to the following steps: The carbon nanotubes hydrophobized by micron-sized polytetrafluoroethylene and cobalt phthalocyanine are mixed in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, and the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and after washing and drying, an amorphous polytetrafluoroethylene-modified molecular catalyst is obtained, wherein: After polytetrafluoroethylene and carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry material, and after standing and drying at room temperature, powdered polytetrafluoroethylene hydrophobic carbon nanotubes are obtained; the powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature of 20-30 degrees Celsius to 400-450 degrees Celsius at a speed of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept warm for 1-3 hours, and then cooled to room temperature of 20-30 degrees Celsius with the furnace to obtain micron-sheet polytetrafluoroethylene hydrophobic carbon nanotubes; after polytetrafluoroethylene and carbon nanotubes are mixed, the mass percentage of polytetrafluoroethylene is 10-30wt%.
8. The method for preparing an amorphous polytetrafluoroethylene-modified molecular catalyst according to claim 7, characterized in that: After polytetrafluoroethylene and carbon nanotubes are mixed, the mass percentage of polytetrafluoroethylene is 20wt%; the mass ratio of carbon nanotubes hydrophobized by micron-sized polytetrafluoroethylene to cobalt phthalocyanine is 15:1; the amount of N,N-dimethylformamide added is (20-25) ml per milligram of cobalt phthalocyanine; the inert protective atmosphere is nitrogen, argon or helium; the powdered polytetrafluoroethylene hydrophobic carbon nanotubes are heated from room temperature of 20-30 degrees Celsius to 400-430 degrees Celsius at a speed of 5-10 degrees Celsius per minute under the inert protective atmosphere and kept warm for 2-3 hours, and then cooled to room temperature of 20-30 degrees Celsius with the furnace.
9. Use of an amorphous polytetrafluoroethylene-modified molecular catalyst as claimed in any one of claims 1 to 6 in electrocatalytic reduction of carbon dioxide to produce carbon monoxide.
10. The use of an amorphous polytetrafluoroethylene modified molecular catalyst in electrocatalytic carbon dioxide reduction to produce carbon monoxide according to claim 9, characterized in that: When in use, the amorphous polytetrafluoroethylene-modified molecular catalyst, FAA solution and DMF are mixed into a uniform solution and sprayed on the gas diffusion electrode as the working electrode (i.e., the catalytic electrode) with a loading of 1-3 mg / cm 2 , using nickel foam loaded with iridium oxide as a counter electrode, power is applied to carry out an electrocatalytic reaction; the electrolyte used is an alkaline solution, such as a 1 mol / L KOH aqueous solution.
Citation Information
Patent Citations
Method for preparing heterogeneous monomolecular electrocatalyst from metal phthalocyanine molecule-nanocarbon and application of heterogeneous monomolecular electrocatalyst
CN110911694A
Gas diffusion electrode for preparing carbon monoxide by electrolyzing carbon dioxide and preparation method of gas diffusion electrode
CN113445064A
Cobalt phthalocyanine-amino carbon nanotube catalyst as well as preparation method and application thereof
CN115652364A
Process for manufacture of a hydrophobic catalyst comprising platinum on carbon and PTFE, hydrophobic catalyst and use thereof
EP4194086A1
Carbon nanotube composite material and conductive material
JP2013082595A